Optimize Image Steganography Based on Distinction Disparity Value and HMPSO to Ensure Confidentiality and Integrity - Ali Salem Ali; Suray Alsamaraee; Aya Ayad Hussein (Journal of Computer Networks and Communications)
To secure the massive amounts of secret messages, the integrity and confidentiality challenges must be addressed. Pressing challenges in the context of a steganography system include security, imperceptibility, and capacity issues. There are trade-offs between payload and security that have been neglected by researchers, as fixing one issue has been indicated to affect the other, and vice versa. To overcome these challenges, a new steganography scheme based on HMPSO and DDV was introduced. The HMPSO is short for Hénon map and particle swarm optimization, while DDV is short for distinction disparity value. The proposed scheme consisted of four phases with different contributions. The first phase was used to preprocess the secret messages and cover images. In this phase, the secret message has been compressed using the Huffman method. The second phase involved the embedding procedure. This phase consists of two different contributions HMPSO and DDV. The HMPSO is responsible for the optimal pixels’ selection. While the DDV is responsible for the embedding process. The third phase involves the extraction method. In extraction, the reverse processes of the previous steps are implemented. Different evaluation parameters have been used to validate and test the proposed scheme such as SSIM, PSNR, HVS, Histogram analysis, and chi-square test. Based on the findings, the proposed scheme has solved the confidentiality and integrity challenges and provides a robust steganography system.